2019
DOI: 10.1039/c9ra09201c
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as a nanofiller for enhancing the tribological properties and thermal conductivity of base grease

Abstract: The addition of graphene-reinforced grease to the mechanical friction surface can effectively reduce the friction coefficient and accelerate heat transportation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In the case of high concentrations of graphene, agglomerates form in the lubricant, which negatively affect the friction surface protection. The resulting tendency to change the wear properties of a lubricant with an increase in graphene concentration is consistent with the results of the research carried out by Fu et al [ 20 ]. According to the published results, with an increase in the concentration of graphene nanoplatelets from 1.00 wt.% to 2.00 wt.%, the diameter of the wear scar decreases, reaching the lowest value for the 2.00 wt.% concentration.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the case of high concentrations of graphene, agglomerates form in the lubricant, which negatively affect the friction surface protection. The resulting tendency to change the wear properties of a lubricant with an increase in graphene concentration is consistent with the results of the research carried out by Fu et al [ 20 ]. According to the published results, with an increase in the concentration of graphene nanoplatelets from 1.00 wt.% to 2.00 wt.%, the diameter of the wear scar decreases, reaching the lowest value for the 2.00 wt.% concentration.…”
Section: Resultssupporting
confidence: 91%
“…The concentration of graphene in the lubricant was 1.00–4.00 wt.%. The best results of the lubricant’s tribological properties were obtained for the graphene concentration in the lubricant of 2.00 wt.% [ 20 ], for which the diameter of the friction scar decreased by approx. 14% compared to the base grease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rGO concentration of 0.4 wt.% reduced the COF by about 20% and 30% for sliding-induced rolling contact and rolling contact compared to base grease. Fu et al [32] tried different graphene additions with calcium grease, and they found that 2 wt.% was the optimum percentage regarding the tribological properties as this percentage reduced the COF by about 15% compared to base grease. Furthermore, a reduction in the friction coefficient by up to 60% was obtained after adding 1 wt.% graphene to a semi-solid lubricant [33].…”
Section: Introductionmentioning
confidence: 99%
“…Exploring how to control friction and reduce wear has important engineering significance and value [1][2][3]. With the rapid development of intelligent mechanical equipment and robot, the demand for regulation and utilization of friction has changed from simply increasing or reducing friction to online reversible intelligent regulation.…”
Section: Introductionmentioning
confidence: 99%